ANALISIS PENURUNAN KINERJA DAYA KELUARAN PADA PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) 5 MWP OELPUAH KUPANG DENGAN MENGGUNAKAN SOFTWARE PVSYST - Yentri Seran; Nursalim Nursalim; Sri Kurniati (Jurnal Media Elektro, 2022)
The Independent Power Plant (IPP) of the Oelpuah Solar Power Plant (SPP) in Kupang Regency has been operating since November 2015 with a 5 MWp. However, the maximum power produced has not yet reached optimal power production, only in the 3,000 - 4,000 kW range. Therefore, a study is needed to identify and analyze the decrease in output power. The measurements in December showed that solar radiation, temperature, and equipment damage significantly affected the decrease in output power by 35.7%. Then, based on the simulation results, the output power produced by the array when tilted at 15° and azimuth 0° is 4,000 kW with an E grid of 9,111 MWh/year. This power will increase to 4,100 kW with an E grid of 9,113 MWh/yr when tilt is 14° and azimuth is -5°. Conversely, a decrease in output power can occur due to changes in tilt and azimuth positions by 0.10%. The other influencing factors are internal factors such as 1.68% inverter losses and 3% solar panel quality losses; meanwhile, in terms of external factors such as solar panel losses due to radiation levels (0.16%), temperature (13.5%), GHI (2.40%), and damaged equipment (25%).